Synthesis Of Nanoparticle Barium Hex Aferrite By Sol Gel Auto Combutio - W Widyastuti; Felly Yulian FF; Rochman Rochiem; Hariyati Purwaningsih (Jurnal Teknik Industri, 2011)
Nanocrystalline of Barium Hexaferrite (BaFe12O19) powders have been synthesized using the sol gel auto combustion method. The ferrite precursors were obtained from aqueous mixtures of Barium nitrate and Ferric nitrate by auto combustion reaction from gel point. These precursors were sintered at different temperatures ranging from 700 to 1000oC for constant calcinations time 2,5 h in a static air atmosphere. Effects of Fe3+/Ba2+ mol ratios and sintering temperatures on the microstructure and magnetic properties were systematically studied. The powders formed were investigated using X-ray diffraction (XRD), scanning electron microscope (SEM) and VSM. The results obtained showed that the phase BaFe12O19 powders were achieved by the Fe3+/Ba2+ mole ratio from the stoichiometric value 11, 11.5 and 12 at temperature 950OC. With increasing of temperature sintering, coercivity and magnetization value tends to rising. The maximum saturation magnetization (66.16 emu/g) was achieved at the Fe3+/Ba2+ mole ratio to 11.5 and the sintering temperature 950OC. The maximum coercivity value 3542 Oe achieved at mole ratio sample 12 with sintering temperature 950OC. Maximum saturation 6616 emu/g achieved at mole ratio sample 115 with the same temperature.